2021
DOI: 10.1111/adj.12835
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for oral lichen planus: A systematic review and network meta‐analysis of randomized clinical trials

Abstract: Background Corticosteroids, calcineurin inhibitors, vitamin D, photodynamic therapy, herbal drugs are some of the interventions tried in clinical trials for treating oral lichen planus. We carried out the present network meta‐analysis to compare the above‐mentioned interventions. Methods Electronic databases were searched for randomized clinical trials evaluating interventions in patients with symptomatic oral lichen planus. Clinical resolution, clinical score, pain resolution, pain score, and adverse effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 58 publications
(49 reference statements)
1
36
0
1
Order By: Relevance
“…Some reviews 33,34 pooled the data of tacrolimus in topical or gargle preparations together, with possible heterogeneity. Some reviews 35,37 pooled the data of topical or systemic drugs together, and review included a few studies with no binding, which may have affected the pooled results. Both studies 33,35 did not explore differences between the individual corticosteroid drug and tacrolimus.…”
Section: Relapsementioning
confidence: 99%
See 1 more Smart Citation
“…Some reviews 33,34 pooled the data of tacrolimus in topical or gargle preparations together, with possible heterogeneity. Some reviews 35,37 pooled the data of topical or systemic drugs together, and review included a few studies with no binding, which may have affected the pooled results. Both studies 33,35 did not explore differences between the individual corticosteroid drug and tacrolimus.…”
Section: Relapsementioning
confidence: 99%
“…Similarly, two previous reviews 33,34 suggested that no difference in the efficacy was noted between tacrolimus and corticosteroids. However, one meta-analysis 35 concluded that topical corticosteroids are the most useful agents for the treatment of OLP, whereas two other studies 36,37 demonstrated that tacrolimus was more effective than corticosteroids. Importantly, the inclusion criteria of previous reviews were different from our review.…”
Section: Relapsementioning
confidence: 99%
“…We identified 26 citations of which 10 systematic reviews (Albedah et al, 2013;Azarpazhooh & Limeback, 2008;Brazzelli et al, 2006;Deepthi & Bilichodmath, 2020;German et al, 2013;Moraschini et al, 2020;Santos et al, 2020;Sharda et al, 2021;Silva et al, 2020;Sridharan & Sivaramakrishnan, 2021) and 16 narrative reviews (Almaz & Sönmez, 2015;Chirumbolo et al, 2021;Domb, 2019;Gupta & Mansi, 2012;Haghighat & Oshaghi, 2020;Lacerda et al, 2021;Lio et al, 2020;Mohammadi et al, 2013;Nogales et al, 2008;Re et al, 2020;Seidler et al, 2008;Suh et al, 2019;Swanson et al, 2021;Tiwari et al, 2017;Trevor Burke, 2012;Tricarico et al, 2020); met the criteria for inclusion in the Map. Most of the reviews were published in the 2008, 2012 and 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Topical corticosteroids are generally considered as first line treatment for the management of symptomatic OLP ( 11 - 13 ). On the other hand, cyclosporine has been investigated as an alternative topical agent for the management of OLP ( 16 , 26 - 45 ).…”
Section: Introductionmentioning
confidence: 99%